Metabolic imprint induced by seed halo-priming promotes a differential physiological performance in two contrasting quinoa ecotypes - Cifuentes, Leonardo; González, Máximo; Pinto-Irish, Katherine; Álvarez, Rodrigo; Coba de la Peña, Teodoro; Ostria-Gallardo, Enrique; Franck, Nicolás; Fischer, Susana; Barros, Gabriel; Castro, Catalina; Ortiz, José; Sanhueza, Carolina; et al. (Frontiers in Plant Science, 2023)
“Memory imprint” refers to the process when prior exposure to stress prepares the plant for subsequent stress episodes. Seed priming is a strategy to change the performance of seedlings to cope with stress; however, mechanisms associated with the metabolic response are fragmentary. Salinity is one of the major abiotic stresses that affect crop production in arid and semiarid areas. Chenopodium quinoa Willd. (Amaranthaceae) is a promising crop to sustain food security and possesses a wide genetic diversity of salinity tolerance. To elucidate if the metabolic memory induced by seed halo-priming (HP) differs among contrasting saline tolerance plants, seeds of two ecotypes of Quinoa (Socaire from Atacama Salar, and BO78 from Chilean Coastal/lowlands) were treated with a saline solution and then germinated and grown under different saline conditions. The seed HP showed a more positive impact on the sensitive ecotype during germination and promoted changes in the metabolomic profile in both ecotypes, including a reduction in carbohydrates (starch) and organic acids (citric and succinic acid), and an increase in antioxidants (ascorbic acid and α-tocopherol) and related metabolites. These changes were linked to a further reduced level of oxidative markers (methionine sulfoxide and malondialdehyde), allowing improvements in the energy use in photosystem II under saline conditions in the salt-sensitive ecotype. In view of these results, we conclude that seed HP prompts a “metabolic imprint” related to ROS scavenger at the thylakoid level, improving further the physiological performance of the most sensitive ecotype.